Urban mobility in the Lisbon Metropolitan Area: a qualitative approach - Ávila Cachado, Rita (2017)
This article results from a research project on inequalities and transportation in the Lisbon Metropolitan Area, and contributes to the scientific debate on the production of urban mobility. Through the analysis of a set of interviews addressed to residents in three municipalities, this study achieves two main goals. First, it describes the main transportation modes in order to identify a general trend toward an increasing use of motorized transport as a consequence of certain stages in the interviewee’s life. Second, it unveils the differentiated factors and reasons behind the choice of using public or private motorized transport. The motives mentioned by interviewees stem from the diverse experiences over their lives, and also from the impact of the current economic and financial crisis, which imposes significant constraints due to the rising costs of the various transportation modes.